Applying block chain to smart home system - Chai, Pei Zhen (2019)
With the advancement of Internet of Things technology nowadays, smart home system is getting more and more popular. Before people starts to install and implement smart home system into their house, they will worry about the security issue embedded within this system. This implies that cyber security of smart home system plays a huge role and needs to be paid attention to. In this project, blockchain technology will be apply on smart home system to enhance the security of existing smart home system because blockchain technology can help to secure integrity, authenticity and auditability of personal data and information. By the nature of blockchain, each block in the chain will be linked with previous block through the help of hash function and changing of transaction records can be detected easily. Additionally, if a block was altered, the whole chain needs to be recomputed through consensus process which was too expensive and almost impossible. Other than that, blockchain also made use of public key cryptography method such that the public key of the data sender will be verified by peer nodes so only authorized parties can access. In this proposed method, it consists of a community of smart homes and only trusted parties can join into this community. Sensor data can be send to server through the aid of local gateway device within each smart homes so that these data can be query out in on-demand basis. Besides, local gateway devices will also help each another to verify a transaction before a request can be successfully enrol. Based on the data stored in the database, users can subscribe to additional service such as healthcare provided by cloud service provider through smart contract established on the consortium blockchain network.